Stalin and the dialect of the Kursk-Orel region: notes on the history of a linguistic enigma - Leonid Kulikov (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2022)
This paper briefly outlines the historical and cultural context of the linguistic discussion about Marxism in linguistics that took place in the Soviet Union in 1950; the materials of the discussion were published in the main Soviet newspaper “Pravda”. I describe the reaction of the academic community to this (undoubtedly incorrect) statement that the Kursk-Orel dialect formed the basis of the Russian national language. The reaction mostly amounted to ritual quotations of this Stalin’s claim (without detailed argumentation) in studies on Russian language and dialectology published by Soviet Slavicists in the 1950s. I discuss proposed explanations for the emergence of the “Kursk-Oryol dialect” theory, in particular, Yu. M. Lotman's hypothesis about the influence of Maxim Gorky's statements on the origin of classical Russian literature in Kursk-Orel steppes as well as several more speculative assumptions. I demonstrate the unsatisfactory character of the proposed explanations and put forward a new hypothesis, which draws attention to the possible influence of F. Engels’ work "The Franconian Dialect".